Effect of modified mold shell on the microstructure and tensile fracture morphology of single-crystal nickel-base superalloy. (5th April 2018) - Xu, Weitai; Zhao, Yutao; Sun, Shaochun; Liu, Manping; Ma, Dexin; Liang, Xiangfeng; Wang, Cunlong; Tao, Ran
Abstract: The mold shell used for single-crystal turbine blades preparation was modified from conventional process to fiber reinforcement technology. The wall thickness was decreased by 32.3 percent (pct) than the conventional process. Then these two mold shells were used to produce single crystal samples of nickel-base superalloy in a Bridgman furnace. The local temperature curves were recorded in the process. The results show that the modified mold shell can increase the temperature gradient in the mushy zone than the conventional mold shell. The primary and secondary dendrite arm space were reduced by 8 pct and 12 pct, respectively. Moreover, both the area fraction and mean size of the γ ′/ γ eutectic were declined, as well as the dendritic segregation tendency. Therefore it contributed to the lower residual eutectic and micro-porosity in the heat-treated microstructure. Further, fracture surface of the samples made by modified mold shell exhibited smaller facets and more uniform dimples in the size and shape.